Is smartphone‐based mood instability associated with stress, quality of life, and functioning in bipolar disorder?. (27th May 2019) - Faurholt‐Jepsen, Maria; Frost, Mads; Busk, Jonas; Christensen, Ellen Margrethe; Bardram, Jakob Eyvind; Vinberg, Maj; Kessing, Lars Vedel
Abstract: Objective: Mood instability in patients with bipolar disorder has been associated with impaired functioning and risk of relapse. The present study aimed to investigate whether increased mood instability is associated with increased perceived stress and impaired quality of life and functioning in patients with bipolar disorder. Methods: A total of 84 patients with bipolar disorder used a smartphone‐based self‐monitoring system on a daily basis for 9 months. Data on perceived stress, quality of life, and clinically rated functioning were collected at five fixed time points for each patient during follow‐up. A group of 37 healthy individuals served as a control comparison of perceived stress, quality of life, and psychosocial functioning. Results: The majority of patients presented in full or partial remission. As hypothesized, mood instability was significantly associated with increased perceived stress (B: 10.52, 95% CI: 5.25; 15.77, P  < 0.0001) and decreased quality of life (B: −12.17, 95% CI. −19.54; −4.79, P  < 0.0001) and functioning (B: −12.04, 95% CI: −19.08; −4.99, P <  0.0001) in patients with bipolar disorder. There were no differences in mood instability according to prescribed psychopharmacological treatment. Compared with healthy individuals, patients reported substantially increased perceived stress and experienced decreased quality of life and decreased functioning based on researcher‐blinded evaluation. Conclusion: Mood instability in bipolar disorder is associated with increased perceived stress and decreased quality of life and functioning even during full or partial remission. There is a need to monitor and identify subsyndromal inter‐episodic symptoms. Future studies investigating the effect of treatment on mood instability are highly warranted.